Evaluation of the Existing Conditions of Tinobu Port, Lasolo District, North Konawe Regency, Southeast Sulawesi Province - Usman, Rizki; Chaerul, Muhammad; Anugrah, Anugrah (Universitas Ibn Khaldun Bogor, 2024)
The research location is located in Tinobu Village, Lasolo District, North Konawe Regency, which is a developing area and is known for its abundant natural wealth. Tinobu Port existed before Indonesia's independence, where Tinobu Port is tens of years old and has become an icon on the coast of North Konawe Regency, especially in Tinobu Village. Tinobu Port does not have any main facilities or supporting facilities that can facilitate activities at the port. Tinobu Port is widely used by local fishermen for loading and unloading of fish to be sold around the North Konawe Regency area and some are even sold as far as the city of Kendari. development after development has been carried out by the surrounding community as well as assistance from the local government so that at this time Tinobu Port already has a causeway with a length of approximately 400 (four hundred) meters, but due to the age factor, the condition of the causeway has also suffered a lot of damage. The purpose of this study was to evaluate the Existing Conditions of Tinobu Port, Lasolo District, North Konawe Regency in the form of several surveys conducted directly at the research location for future development purposes.